Long-term survival after heart transplantation: The Experience of the Republic of Serbia Heart transplantation program - Matkovic, Milos; Nestorovic, Emilija; Bilbija, Ilija; Aleksic, Nemanja; Markovic, Dejan; Putnik, Svetozar (Medical Research, 2023)
Introduction/Aim: Heart transplantation (HTX) is the golden standard for treatment of patients in symptomatic terminal stadium of heart failure. This study aimed to investigate the long-term results of the HTX and to determine the independent predictors of survival after HTX within the Serbian heart transplantation program.Methods: The retrospective observational study was performed. The study included 44 patients that were subjected to heart transplantation form 2013-2021 within The Republic of Serbia Heart Transplantation Program. All patients were listed to the National heart transplantation waiting list according to the contemporary ISHLT criteria. The study included all the patients subjected to HTX, as well as the ones that were om long-term circulatory support preoperatively. The data has been obtained from the medical history records and follow-up visits. Results: The average survival of all patients was 1611.8 days (1306.9-1916.7). The median length of patient follow-up was 637.4 days (1-2028 days). Six-year patient survival was 70.5%.Cox's regression analysis determined that the following were independent predictors of worse outcome: age of the recipient, body mass index of the recipient, previous CVI, preoperative chronic renal insufficiency, pulmonary hypertension, infection in the postoperative course, as well as the need for mechanical circulatory support in the immediate postoperative course. Conclusion: The Serbian Heart Transplantation program demonstrated the survival rate comparable to the HTX centers worldwide and in ISHLT registry. The independent risk factors should be carefully analyzed for our study population and taken into consideration for the procedure planning.
Keywords: heart transplantation; survival; independent predictors